2019
DOI: 10.1021/acs.jpcc.9b06366
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Confined Methane Hydrate in Hydrophilic and Hydrophobic Model Carbons

Abstract: Methane hydrate confined in porous materials is postulated as an alternative energy storage strategy. By applying model carbons with ordered and uniformly sized pores and a combination of advanced in situ characterization techniques, we address fundamental questions on the formation mechanism of methane hydrate in confinement. Here, we provide experimental evidence for the presence of methane hydrate inside confined spaces by in situ small- and wide-angle neutron scattering, X-ray diffraction, and high-pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 40 publications
5
72
0
Order By: Relevance
“…Apparently, methane physical adsorption in micropores contributes to methane uptake in the first stage, which is almost nil because of steric restriction. However, it significantly depends on the chemical properties of the AC surface, and since strong water molecule–AC surface interaction enhances steric restriction, hydrophobic carbon materials were known as adsorbing more methane (Casco et al, 2019 ), and some porous materials were even reported to have no influence on methane physical adsorption (Casco et al, 2016 ). Subsequently, when pressure exceeds a threshold value, i.e., equilibrium pressure, drastic methane uptake occurs that associates with hydrate formation at large pores or pore mouths.…”
Section: How Methane Would Be Adsorbed On Pw-acmentioning
confidence: 99%
See 3 more Smart Citations
“…Apparently, methane physical adsorption in micropores contributes to methane uptake in the first stage, which is almost nil because of steric restriction. However, it significantly depends on the chemical properties of the AC surface, and since strong water molecule–AC surface interaction enhances steric restriction, hydrophobic carbon materials were known as adsorbing more methane (Casco et al, 2019 ), and some porous materials were even reported to have no influence on methane physical adsorption (Casco et al, 2016 ). Subsequently, when pressure exceeds a threshold value, i.e., equilibrium pressure, drastic methane uptake occurs that associates with hydrate formation at large pores or pore mouths.…”
Section: How Methane Would Be Adsorbed On Pw-acmentioning
confidence: 99%
“…However, because of complicated surface properties and pore texture, the micronature behind the macromechanisms is still unclear. One of the most appreciated factors was reported to be the chemical properties of AC surface, e.g., surface defect (Pirzadeh and Kusalik, 2013 ) and hydrophobic or hydrophilic properties (Casco et al, 2017 , 2019 ; Nguyen et al, 2017 ), which can change the interaction between water molecules and AC surface. Water molecules are known to assemble at the sites which are occupied by surface-deflecting and oxygen-containing functional groups to form clusters, which may provide potential nucleation sites and constitute a hydrate precursor.…”
Section: How Methane Would Be Adsorbed On Pw-acmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches have been tested to increase the gas-liquid contact area, and consequently the rate of MH formation (Linga et al 2009;Mel'nikov et al 2016;Park and Kim 2013). Nanoporous materials have proven to be an excellent platform for hosting and promoting the formation of MHs in a matter of minutes (Borchardt et al 2018;Casco et al 2019). Still, there is little known on how surfaces can be used to facilitate MH growth.…”
Section: Vapor/gas Sorptionmentioning
confidence: 99%